Implementasi Sistem Sanksi Dua Jalur (Double Track System) Bagi Korporasi Dalam Tindak Pidana Kekerasan Seksual Di Lingkungan Kerja - Britney Lauren (Jurnal Hukum Lex Generalis, 2024)
Sexual violence is a serious and complex form of human rights violation, with profound impacts on individuals and society. Apart from the condition of society which has not yet adapted to the development of sexual crimes, criminals have also experienced significant developments. In the development of crime today, the perpetrators are not only committed by humans but also by companies or corporations. However, Law Number 12 of 2022 concerning Crimes of Sexual Violence does not provide clear criteria regarding the regulation of corporate responsibility for crimes of sexual violence. This research formulates the problem, namely: 1. How is corporate criminal liability regulated for criminal acts of sexual violence in the work environment? and 2. What is the double track system model of punishment for corporations in criminal acts of sexual violence based on Law Number 12 of 2022? This type of research is normative research that uses a statutory approach and a conceptual approach and uses library sources as secondary data in the research process. The results of this research show that corporations have been regulated as legal subjects and can be charged with criminal liability for sexual violence, as long as the corporation fulfills the elements of offense in Supreme Court Regulation Number 13 of 2016, namely that the corporation allows criminal acts to occur and does not take steps to prevent the crime from occurring. bigger. Then, for corporations, Law Number 12 of 2022 has adopted a double track system model of punishment, so that criminal sanctions and additional sanctions can be applied. So the conclusion is that corporations can be burdened with criminal liability and can be given criminal sanctions in accordance with the provisions of Law Number 12 of 2022.